A predictive model of loss time due to low back pain among garment sewers in Bulacan - Lugay, Carlos Ignacio P.
Filipinos have been used to seeing small tailoring and ladies garment shops in almost every corner of the street. And in almost all households, there is usually a manually-operated sewing machine in one corner of the house. In fact, to emphasize how skilled the Filipinos are in garments assembly, garments export has been the country's number tow export since the early 80's.